THE DEVELOPMENT OF A VILLAGE POTENTIAL INFORMATION SYSTEM IN BATUKARAS VILLAGE, CIJULANG DISTRICT, PANGANDARAN REGENCY - Agriva Ginting, Kevin
The development of the Batukaras Village Potential Information System based on WebGIS is a strategic effort to integrate village data for use by both village officials and the community. Data collection is conducted comprehensively using technologies such as Unmanned Aerial Vehicle (UAV) Photogrammetry, Global Navigation Satellite System (GNSS), Multibeam Echosounder (MBES), and field verification for geospatial data, while nongeospatial data is obtained with the assistance of village officials. This data is then processed into various thematic products using specialized methods and visualized in a WebGIS-based village potential information system. This WebGIS will include information such as village profiles, natural resource statistics, human resource statistics, as well as infrastructure. These products include a Digital Elevation Model, Land Cover and Land Use Map, Bathymetric Map, LOD 2 Building Map, Land Parcel Map, Tsunami Hazard Map, and Flood Hazard Map. With this village potential information system, the Batukaras Village government can more easily determine policies and development directions, and the broader community can better understand the potential of Batukaras Village.